2021
DOI: 10.1002/prp2.755
|View full text |Cite
|
Sign up to set email alerts
|

Drp1‐dependent peptide reverse mitochondrial fragmentation, a homeostatic response in Friedreich ataxia

Abstract: Friedreich ataxia is an autosomal recessive, neurodegenerative disease characterized by the deficiency of the iron‐sulfur cluster assembly protein frataxin. Loss of this protein impairs mitochondrial function. Mitochondria alter their morphology in response to various stresses; however, such alterations to morphology may be homeostatic or maladaptive depending upon the tissue and disease state. Numerous neurodegenerative diseases exhibit excessive mitochondrial fragmentation, and reversing this phenotype impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…We previously reported that FRDA patient fibroblasts displayed high amounts of fragmented mitochondrial networks, accompanied by clustering of Dynamin-related protein 1 (Drp1) phosphorylated at its (Ser616) residue at the fragmentation sites ( Johnson et al, 2021 ). Thus, to assess if frataxin knockdown manifests mechanistic similarities with in vitro experiments and leads to increases in pDrp1 in the FRDA cerebellum, we analyzed the cerebellum at different stages of induction in FRDAkd mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that FRDA patient fibroblasts displayed high amounts of fragmented mitochondrial networks, accompanied by clustering of Dynamin-related protein 1 (Drp1) phosphorylated at its (Ser616) residue at the fragmentation sites ( Johnson et al, 2021 ). Thus, to assess if frataxin knockdown manifests mechanistic similarities with in vitro experiments and leads to increases in pDrp1 in the FRDA cerebellum, we analyzed the cerebellum at different stages of induction in FRDAkd mice.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue pathology was assessed by performing immunohistochemical studies following the procedure previously described ( Lin et al, 2014 ; Johnson et al, 2021 ). The paraffin-embedded brain and DRG sections were deparaffinized, rehydrated, and antigen-retrieved in antigen unmasking solution (Vector Laboratories) and then subject to the immunostaining procedure.…”
Section: Methodsmentioning
confidence: 99%
“…SS-31 has also been reported to reverse mitochondrial fragmentation in patients with mitochondrial disease. 30,41…”
Section: Discussionmentioning
confidence: 99%
“…SS-31 has also been reported to reverse mitochondrial fragmentation in patients with mitochondrial disease. 30,41 Mitochondria are known to produce significant amounts of ROS that may contribute to intracellular oxidative stress. 56 ROS have been reported to be associated with tendon pathology, including pathologic tendon calcification, 69 and the accumulation of ROS leading to oxidative stress has been implicated as a mediator of age-related rotator cuff tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo models of FRDA include yeast, nematode worm, fruit fly, and mice ( Babcock et al, 1997 ; Radisky et al, 1999 ; Puccio et al, 2001 ; Al-Mahdawi et al, 2004 ; Vázquez-Manrique et al, 2006 ; Virmouni et al, 2014 ; Monnier et al, 2018 ), whereas FRDA in vitro models include patient-derived cells such as immortalized lymphoblastoid cells, primary fibroblasts ( Li et al, 2016 ; Agro and Diaz-Nido, 2020 ; Misiorek et al, 2020 ; Johnson et al, 2021 ), FRDA-derived iPSCs ( Angulo et al, 2021 ; Kelekci et al, 2021 ), and iPSC-based models such as neurons, cardiomyocytes, and beta cells ( Crombie et al, 2016 ; Schreiber et al, 2019 ) ( Figure 1 ). All these FRDA models need to imitate the symptoms of FRDA patients.…”
Section: Introductionmentioning
confidence: 99%